A study of urban heat island of Banda Aceh City, Indonesia based on land use/cover changes and land surface temperature - Ashfa Achmad; Laina Hilma Sari; Ichwana Ramli (Aceh International Journal of Science and Technology, 2019)
This article described the spatial and temporal of land surface temperature (LST) patterns in Banda Aceh City, Indonesia, in the context of urban heat island (UHI) phenomenon. Landsat imaginary in 1998 and 2018 was used in this study, which represents the conditions before and after the tsunami. Geographic Information System (GIS) and Remote Sensing (RS) technique were used for data analysis. The 1998 and 2018 LUC maps were derived from remote sensing satellite images using a supervised classification method (maximum likelihood). Both LUC maps contained five categories, namely built-up area, vegetation, water body, vacant land, and wet land. The 1998 LUC map had a kappa coefficient 0.91, while the 2018 LUC map had 0.84. It was found that the built-up area increased by 100%, while the vegetation category fell 50%. The overall mean LST in the study area increased 5.90C between 1998 and 2018, with the highest mean increase in the built-up area category. The study recommends that LST should be taken into consideration in urban planning process to realize sustainable urban development. It also emphasizes the importance of optimizing the availability of green open space to reduce UHI effects and helps in improving the quality of the urban environment.